Complications after advanced ovarian cancer surgery—A population‐based cohort study. (11th April 2022) - Palmqvist, Charlotte; Michaëlsson, Hanna; Staf, Christian; Johansson, Mia; Albertsson, Per; Dahm‐Kähler, Pernilla
Abstract: Introduction: Surgical complications after primary or interval debulking surgery in advanced ovarian cancer were investigated and associations with patient characteristics and surgical outcomes were explored. Material and methods: A population‐based cohort study including all women with ovarian cancer, FIGO III–IV, treated with primary or interval debulking surgery, 2013–2017. Patient characteristics, surgical outcomes and complications according to the Clavien–Dindo (CD) classification system ≤30 days postoperatively, were registered. Uni‐ and multivariable regression analyses were performed with severe complications (CD ≥ III) as endpoint. PFS in relation was analyzed using the Kaplan–Meier method. Results: The cohort included 384 women, where 304 (79%) were treated with primary and 80 (21%) with interval debulking surgery. Complications CD I–V were registered in 112 (29%) patients and CD ≥ III in 42 (11%). Preoperative albumin was significantly lower in the CD ≥ III cohort compared with CD 0–II ( P  = 0.018). For every increase per unit in albumin, the risk of complications decreased by a factor of 0.93. There was no significant difference in completed chemotherapy between the cohorts CD 0–II 90.1% and CD ≥ III 83.3% ( P  = 0.236). In the univariable analysis; albumin <30 g/L, primary debulking surgery, complete cytoreduction and intermediate/high surgical complexity score (SCS) were associated with CD ≥ III. In the following multivariable analysis, only intermediate/high SCS was found to be an independent significant prognostic factor. Low ( n  = 180) vs intermediate/high SCS ( n  = 204) showed a median PFS of 17.2 months (95% confidence interval [CI] 15.2–20.7) vs 21.5 months (95% CI 18.2–25.7), respectively, with a significant log‐rank; P  = 0.038. Conclusions: Advanced ovarian cancer surgery is associated with complications but no significant difference was seen in completion of adjuvant chemotherapy when severe complications occur. Importantly, our study shows that intermediate/high SCS is an independent prognostic risk factor for complications. Low albumin, residual disease and primary debulking surgery were found to be associated with severe complications. These results may facilitate forming algorithms in the decision‐making procedure of surgical treatment protocols.